[SOLVED] How to prove reduction of this induction to formula?
Difference between en2 and en3, changed 9 character(s)
$a_1 = 1$  ↵
$a_2 = 5$  ↵
$a_n = a_{n-1} + n^2(a_{n-2}+1)$↵

**Prove** $a_n=(n+1)!-1$  ↵
P.S. [Original problem](https://artofproblemsolving.com/wiki/index.php/Induction#Intermediate) 

History

 
 
 
 
Revisions
 
 
  Rev. Lang. By When Δ Comment
en3 English NewFlow 2019-06-16 11:32:59 9
en2 English NewFlow 2019-06-16 10:40:58 99
en1 English NewFlow 2019-06-16 10:33:13 138 Initial revision (published)